Efektivitas Daya Hambat Ekstrak Mengkudu (Morinda citrofolia L.) terhadap Pertumbuhan Lactobacillus acidophilus: Studi in vitro - Meyrisa Bastari; Dhandi Wijaya; Ismalayani Ismalayani (Jurusan Keperawatan Gigi, Poltekkes Kemenkes Palembang, 2022)
Dental caries is a disease of the hard tissues of the teeth which until now cannot be cured. However, the process of worsening due to this disease can be anticipated by patching or removing it. Preventive measures against this disease must be able to intervene in at least one of the factors causing caries, one of which is Lactobacillus acidophilus. Noni fruit (Morinda citrofolia L.) which is an endemic plant in Indonesia, including South Sumatra, contains scopoletin which is bacteriostatic against Lactobacillus and can prevent the attachment of Lactobacillus acidophilus to the acquired pellicle on the tooth surface, thereby reducing the risk of dental caries. This research is an experimental study with a post test-only control group design. Noni extracts at concentrations of 20%, 40%, and 80% were tested for their inhibition on the growth of Lactobacillus acidophilus on de Man Rogosa Sharpe (MRS) agar media with 1% iodine as a positive control and 70% alcohol as a negative control. Data were analyzed using One-Way Anova test. Noni extract at concentrations of 20%, 40%, and 80% effectively inhibited the growth of Lactobacillus acidophilus with an average zone of inhibition of 7.2 mm, 8.3 mm, and 11.2 mm, respectively. Noni extract 80% was even more effective in inhibiting the growth of Lactobacillus acidophilus than the positive control.